THE TRANSFER PROBLEM IN INDONESIA AND POLICY RESPONSES - Asmara, Amri Anjas (Journal of Indonesian Economy and Business, 2012)
This paper examines the implications of, and policy responses to the transfer problem phenomenon, which is the interaction between surging capital inflows and real exchange rate. In particular, this paper identifies three episodes of large net private capital inflow to Indonesia during 1995 - 2010. Episodes of large capital inflows are often associated with real exchange rate appreciations. In turn, these conditions could undermine economic competitiveness in terms of price.This paper adopts theoretical framework that leads to test the long-run co-movements of real exchange rates and capital inflows. This long run relationship is modeled on thecointegration framework. The Full-Modified Ordinary Least Square (FMOLS) is used to provide optimal estimates of cointegration regressions, dealing with endogeneity andserial correlation effect in the regressors that result from the existence of the cointegrating relationships.Controlling for relative output levels, degree of openness, and the terms of trade, time series empirical evidence presented evidence supporting the existence of a significanttransfer problem in Indonesia. Moreover, using disaggregated measure of inflows, this paper finds that portfolio investment has the most significant impact on REER appreciationin Indonesia.A comprehensive assessment of various policy responses to the transfer problem leads to two major conclusions. First, the problematic relationship between REER apreciationand capital inflows would be more moderate in which the authorities exercised countercyclical fiscal. It means that greater fiscal restraint would also help ease pressures for real appreciation of the exchange rate. Second, aggressive sterilization could be the first line of defense against REER apreciation during surge of capital inflows.Keywords: Transfer Problem, Real Effective Exchange Rate, Capital Inflows, Cointegration, Full-Modified Ordinary Least Squared (FMOLS)